Antioxidant activities of plant extracts and essential oil-cyclodextrin complexes and their effect on lipid accumulation in porcine adipocytes in vitro - Rakkiat Norkeaw; Chaiwat Arjin; Apinya Sartsook; Niraporn Chaiwang; Supamit Mekchay; Sarana Rose Sommano; Warintorn Ruksiriwanich; Korawan Sringarm (Veterinary Integrative Sciences, 2021)
Fat deposition is important for pig production because excessive fat decreases the economic value of meat production. Plant extracts have been used as feed additive in pig diets to improve oxidative stability of meat. However, only a few studies had investigated the effect of plant extracts on lipid accumulation of porcine adipocytes. Therefore, this study examined antioxidative potential of plant extracts and essential oil-cyclodextrin complexes and their effect on lipid accumulation in porcine adipocytes. Porcine preadipocytes were isolated from dorsal subcutaneous adipose tissue of a 5-month-old female pig. Preadipocytes were differentiated in the presence of extracts, then lipid accumulation was determined using oil red O staining. Results showed that green tea and grape seed extracts had the highest total phenolic and total flavonoid contents and also possessed the highest antioxidant activities. Among essential oil-cyclodextrin complexes, thyme oil had the highest antioxidant activities by all assays. With a regard to the lipid accumulation, all of plant extracts and essential oil-cyclodextrin complexes decreased lipid accumulation in adipocytes from 32.61 to 91.71% compared with the control. Green tea extract, thyme and galangal oil products decreased lipid accumulation about 60% lower than that of the control. In conclusion, green tea and grape seed extracts, and thyme oil powder illustrated high antioxidant potentials, while lipid accumulation in porcine adipocytes was greatly reduced by green tea extract, thyme and galangal oil products. The research finding is beneficial in the development of natural feed additives to improve oxidative stability and reduce excessive subcutaneous fat in pig production.